Primary systemic sclerosis heart involvement: A systematic literature review and preliminary data-driven, consensus-based WSF/HFA definition. Issue 1 (February 2022) - Bruni, Cosimo; Buch, Maya H; Furst, Daniel E; De Luca, Giacomo; Djokovic, Aleksandra; Dumitru, Raluca B; Giollo, Alessandro; Polovina, Marija; Steelandt, Alexia; Bratis, Kostantinos; Suliman, Yossra Atef; Milinkovic, Ivan; et al.
Introduction: Primary heart involvement in systemic sclerosis may cause morpho-functional and electrical cardiac abnormalities and is a common cause of death. The absence of a clear definition of primary heart involvement in systemic sclerosis limits our understanding and ability to focus on clinical research. We aimed to create an expert consensus definition for primary heart involvement in systemic sclerosis. Methods: A systematic literature review of cardiac involvement and manifestations in systemic sclerosis was conducted to inform an international and multi-disciplinary task force. In addition, the nominal group technique was used to derive a definition that was then subject to voting. A total of 16 clinical cases were evaluated to test face validity, feasibility, reliability and criterion validity of the newly created definition. Results: In total, 171 publications met eligibility criteria. Using the nominal group technique, experts added their opinion, provided statements to consider and ranked them to create the consensus definition, which received 100% agreement on face validity. A median 60(5–300) seconds was taken for the feasibility on a single case. Inter-rater agreement was moderate (mKappa (95% CI) = 0.56 (0.46–1.00) for the first round and 0.55 (0.44–1.00) for the second round) and intra-rater agreement was good (mKappa (95% CI) = 0.77 (0.47–1.00)). Criterion validity showed a 78 (73–84)% correctness versus gold standard. Conclusion: A preliminary primary heart involvement in systemic sclerosis consensus-based definition was created and partially validated, for use in future clinical research.